Bugis Capitalism: Business Ethics Based on Local Wisdom - Ahmadin (Research Agency for Humanity and Urban, 2023)
For quite a long time, the world community has generally only known two main types of motivation for capitalism, namely the Protestant Ethic, which was written about through Max Weber's book, and Tokugawa Religion, which was introduced through the writings of Robert N. Bellah. This book discusses the spirit of capitalism which originates from local wisdom, namely siri' in the Bugis community in South Sulawesi, Indonesia, which is extracted from the book Bugis Capitalism. In contrast to the two spirits of Weber-style capitalism and the Bellah style which are motivated by religious values, Bugis capitalism is actually motivated by local wisdom which originates from messages from ancestors or wise people. The practice of ancestral messages as a social system has made the Bugis people successful as entrepreneurs both in their own villages and in overseas areas.